TRANSITION STRENGTHS OF GAMMA RAYS FROM EXCITED LEVELS OF 90 Te NUCLEUS - Jassim, Fatima (Iraqi Journal of Science, 2024)
Transition strengths for y- transitions from the excited levels in Te nucleus have been calculated; y-ray branchings and multipole mixing ratios values for gamma transitions are used together with mean life times for these levels to calculate the transitions strengths of y-transitions In general, the present results are compared with other theoretical results based on different nuclear models and given a reasonable agreement